Influential factors on patient satisfaction and effectiveness of health promotion in primary healthcare Xi'an China - Li, Huan (2024)
Patient satisfaction is an important indicator for evaluating the healthcare system and predicting health outcomes, gaining a deep insight into patient needs, expectations, and experiences is crucial for enhanced healthcare quality. Health promotion can effectively help people change their lifestyle, achieve the best physical, emotional, and other aspects of health, and play an important role in primary healthcare. Xi'an, as a capital city in western China, faces the dual challenges of population growth, diversified medical demand and efficient allocation of medical resources. Especially after the outbreak of COVID-19, Xi 'an's primary healthcare institutions have been pushed to the front line of epidemic prevention and control, face the challenges of assessing and managing COVID-19 patients in a larger population setting with limited resources in comparison to hospitals. However, so far, there is still a lack of research on the patient satisfaction with primary healthcare in Xi 'an, and the effectiveness of health promotion intervention on patient satisfaction is still limited.